N,S-Co-doped TiO2 Nanophotocatalyst: synthesis, electronic structure and photocatalysis - Sathish, M.; Viswanath, R. P.; Gopinath, Chinnakonda S. (Journal of Nanoscience and Nanotechnology, 2009)
N,S-co-doped anatase-phase TiO2 (N,S-TiO2) nanophotocatalysts were prepared from either benzothiazoline or aminothiol with titanium isopropoxide followed by a systematic thermal decomposition. The chemical nature of S and N in N,S-TiO2 have been identified by XPS to be sulfate and NO-like, respectively. A significant band broadening and red-shift in the UV-visible absorption spectrum of N,S-TiO2 suggests a band gap reduction compared to TiO2. A maximum band-gap narrowing of 0.22 +/- 0.02 eV was observed on N,S-TiO2. Higher energy width observed on N,S-TiO2 is in contrast to 0.13 eV from N-doped TiO2 indicating the sulfate-like species might play a major role in narrowing the band-gap to a Higher level. It is confirmed that the oxidation of N and S to NO and SO42- occurs in the final stage of preparation of N,S-TiO2, during calcination in air. It is predicted that the oxygen associated with sulfate and NO structural features could be crucial in bringing down the energy gap and red shift in optical absorption and the role of sulfur is to facilitate the above. Photocatalytic decomposition of methylene blue has been carried out on N,S-TiO2 shows higher activity than the commercial TiO2 in the visible region. However, sulfate species seems to enhance the activity of N,S-TiO2 marginally compared to N-TiO2, and possible suggestions are given to improve the same.
Keywords: nitrogen; Photocatalyst; Sulfur; TiO2; Visible Light Absorption

Photocatalytic mineralization of benzene over gold containing titania nanotubes: role of adsorbed water and nanosize gold crystallites - Awate, S. V.; Sahu, R. K.; Kadgaonkar, Mahesh D.; Kumar, R.; Gupta, N. M. (Catalysis Today, 2009)
Well aligned titania nanotubes, with surface area of similar to 150 m(2) g(-1) and average pore diameter of similar to 5 nm, have been synthesized by subjecting a mesoporous TiO(2) sample to alkaline treatment followed by calcination at different temperatures. Composite catalysts with gold particles dispersed in these nanotubes were also synthesized and their structural, morphological, optical and photocatalytic properties were examined. The catalytic activity of TiO(2) for UV-mediated photo-oxidation of benzene was found to be affected by several factors, such as the sample texture. presence of adsorbed water and gold crystallites. The overall conversion of benzene to form CO(2) followed a trend: Au/nanotube > TiO(2) nanotubes > mesoporous TiO(2). In situ IR spectroscopy revealed that the adsorption and reaction of benzene molecules gave rise to formation of certain phenolic species over TiO(2), while the temperature-programmed desorption (TPD) study showed that the Au/TiO(2) interfaces serve as distinct sites for the adsorption and activation of oxygen molecules. It is suggested that certain hydroxyl and oxygen ion radicals produced under UV-irradiation may promote the deep oxidation of surface phenolic species and phenoxyl (ArO center dot) type transient radicals. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Benzene degradation; Gold containing; Photocatalyst; Role of adsorbed water; TiO(2) nanotubes; Transient species

Enhanced photocatalytic activity of multi-doped TiO2 for the degradation of methyl orange - Charanpahari, A.; Umare, S. S.; Gokhale, S. P.; Sudarsan, V.; Sreedhar, B.; Sasikala, R. (Applied Catalysis A-General, 2012)
We report the synergistic effect of dopants like Gd, N and Sin enhancing the photocatalytic activity of TiO2. Nanosized TiO2 doped at both cationic and anionic sites by Gd, N and S exhibited increased photocatalytic activity compared to TiO2 doped with either Gd or N and S. All the doped TiO2 existed as anatase phase and no separate phase due to Gd2O3 was seen up to a Gd concentration of 2%. The particle size as seen from the transmission electron micrograph was similar to 25 nm. The optical absorption property of TiO2 was improved by doping and redshift of the absorption edge is seen for all doped samples compared to pristine TiO2. The red shift of the absorption edge was the highest for the multiple ion-doped sample. Presence of bonded N and S in TiO2 was detected by X-ray photoelectron spectroscopy. Fluorescence lifetime studies indicated an enhanced lifetime for the charge carriers in the doped system compared to pristine TiO2. Photocatalytic activity study showed that the multi-doped sample has the highest activity for the degradation of methyl orange compared to Gd-TiO2, NS-TiO2 and pristine TiO2. The enhanced photocatalytic activity of the multi-doped TiO2 is attributed to factors such as improved optical absorption property and improved lifetime of the charge carriers. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Fluorescence lifetime; Gd N S doped TiO2; Methyl orange; Photocatalyst; Photodegradation

Factors affecting the production of H-2 by water splitting over a novel visible-light-driven photocatalyst GaFeO3 - Dhanasekaran, P.; Gupta, N. M. (International Journal of Hydrogen Energy, 2012)
A d(10) photocatalyst, GaFeO3 having a band gap of similar to 2.7 eV, exhibits significant activity for the overall splitting of water under visible light (>395 nm) irradiation, in the absence of sacrificial reagent or a noble metal co-catalyst. The doping of an anion led to considerable enhancement in activity, the S-doped catalysts displaying better activity compared to the samples containing nitrogen. Even though the H-2/O-2 yields were affected by preparation-dependent grain morphology, no direct relationship was observed between the photoactivity of a sample and its specific surface area. The techniques of HRTEM, SEM, XPS, Laser Raman, UV-visible and photoluminescence spectroscopy have enabled to demonstrate that, besides the grain morphology, certain lattice imperfections and microstructure may also play a crucial role in water splitting activity of a photocatalyst. The factors responsible for catalyst deactivation are examined. Copyright (C) 2011, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: GaFeO3; hydrogen production; Microstructure; Photocatalyst; water splitting

Direct thermal polymerization approach to N-rich holey carbon nitride nanosheets and their promising photocatalytic H-2 evolution and charge-storage activities - Antil, Bindu; Kumar, Lakshya; Reddy, K. P.; Gopinath, C. S.; Deka, Sasanka (ACS Sustainable Chemistry & Engineering, 2019)
Energy conversion and energy storage are two crucial challenges in green chemistry that have attracted tremendous attention for the last several decades. In this work, we have addressed both issues by synthesizing nitrogen-rich, few-layer-thick holey graphitic carbon nitride (g-C3N4) nanosheets by a simple, novel, direct thermal polymerization method, which is found to be very good in photocatalytic H-2 evolution reaction (energy-conversion) and charge-storage supercapacitor (energy-storage) applications. This as-synthesized conjugated polymer semiconductor (obtained stoichiometry C3N4.8) with unique structural and morphological advantages exhibits superior photocatalytic water splitting activity to H-2 evolution (2 620 mu mol h(-1) g(-1)) without the help of any cocatalysts under visible light in the presence of 20% triethanolamine (TEOA). The calculated apparent quantum yield is 8.5% at 427 nm, and the rate of photocatalytic hydrogen generation remained constant for nine consecutive catalytic cycles (9 h photocatalysis). The present material also shows electrochemical double layer capacitor (EDLC) behavior in alkaline electrolyte, where a symmetric coin cell device consisting of this electrode material without any large area support or conductive filler delivers high specific capacitance (275 F g(-1)), energy density (30 Wh kg(-1)), and power density (6651 W kg(-1)), and the supercapacitor cell can retain >98% capacitance efficiency up to 10 000 measured cycles at various current densities.
Keywords: g-C3N4; Hydrogen evolution; nanosheets; Photocatalyst; supercapacitor; water splitting

Durable metalloporphyrin 2D-polymer for photocatalytic hydrogen and oxygen evolution from river and sea waters - Ranjeesh, Kayaramkodath Chandran; George, Leena; Maibam, Ashakiran; Krishnamurty, Sailaja; Babu, Sukumaran Santhosh (ChemCatChem, 2021)
It is highly imaginary that the outcome of a combination of two complementary resources leads to answer an alarming global issue. One such possible example is the solar seawater splitting for `clean fuel' H-2 generation. Since the catalytic activity and stability of the photocatalysts are substantially challenged in seawater, the design of an efficient and stable photocatalyst is highly desirable. Herein, we demonstrate the solar seawater splitting by a two-dimensional polymer catalyst derived from metalloporphyrin bearing multi-hydroxyl groups. A bimetallic (Co and Ni) porphyrin 2D-polymer exhibits excellent long-term durability of 15 cycles of H-2 and O-2 generation in 200 days from pure water without a considerable decrease in efficiency. Detailed studies using river and seawaters also show the reliable performance of the catalyst over repeated cycles. Here the deactivation modes of catalytic activity have been nullified by the layered metalloporphyrin polymer structure through stable pi-pi stacking, signifying the molecular design of 2D-polymer photocatalyst.
Keywords: 2D-polymer; Photocatalyst; porphyrin; Self-assembly; water splitting

One-dimensional multichannel g-C3N4.7 nanostructure realizing an efficient photocatalytic hydrogen evolution reaction and its theoretical investigations - Antil, Bindu; Kumar, Lakshya; Ranjan, Ravi; Shenoy, Sulakshana; Tarafder, Kartick; Gopinath, Chinnakonda S.; Deka, Sasanka (ACS Applied Energy Materials, 2021)
The emerging metal-free carbon nitride (C3N4) offers prominent possibilities for realizing the highly effective hydrogen evolution reaction (HER). However, its poor surface conductivity and insufficient catalytic sites hinder the HER performance. Herein, a one-dimensional vermicular rope-like graphitic carbon nitride nanostructure is demonstrated that consists of multichannel tubular pores and high nitrogen content, which is fabricated through a cost-effective approach having the final stoichiometry g-C3N4.7 for HER application. The present g-C3N4.7 is unique owing to the presence of abundant channels for the diffusion process, modulated surface chemistry with rich- electroactive sites from N-electron lone pairs, greatly reduced recombination rate of photoexcited exciton pairs, and a high donor concentration (4.26 x 10(17) cm(3)). The catalyst offers a visible-light-driven photocatalytic H-2 evolution rate as high as 4910 mu mol h(-1)g(-1) with an apparent quantum yield of 14.07% at band gap absorption (2.59 eV, 479 nm) under 7.68 mW cm(-2) illumination. The number of hydrogen gas molecules produced is 1.307 x 10(15) s(-1) cm(-2), which remained constant for a minimum of 18 h of repeated cycling in the HER without any degradation of the catalyst. In density functional theory calculations, a significant change in the band offset is observed due to N doping into the system in favor of electron catalysis. The theoretical band gap of a monolayer of g-C3N4.7 was enormously reduced because of the presence of additional densities of states from the doped N atom inside the band gap. These impurity or donor bands are formed inside the band gap region, which ultimately enhance the hydrogen ion reduction reaction enormously.
Keywords: carbon nitride; Density functional theory; hydrogen evolution reaction; nitrogen-rich; Photocatalyst

Enhanced hydrogen fuel production using synergistic combination of solar radiation and TiO2 photocatalyst coupled with Burkholderia cepacia lipase - de Souza Brandao, Luma Mirely; Barbosa, Milson dos Santos; de Jesus, Roberta Anjos; Bharad, Pradnya Arunrao; Lima, Alvaro Silva; Faria Soares, Cleide Mara; Navarro Yerga, Rufino Manuel; Bilal, Muhammad; Romanholo Ferreira, Luiz Fernando; Iqbal, Hafiz M. N.; Gopinath, Chinnakonda S.; Figueiredo, Renan Tavares (International Journal of Hydrogen Energy, 2022)
Promising and sustainable alternatives for hydrogen production have been investigated. Among these, the use of enzymes may represent an efficient alternative. In this work, an increase in hydrogen production under simulated sunlight by combining TiO2 and TiO2/MgCl2 with Burkholderia cepacia lipase (BCL) was reported. The samples (TiO2, TiO2/MgCl2, and TiO2 /MgCl2/BCL) were characterized by X-ray diffraction (XRD), thermo-gravimetric (TGA), N-2 adsorption-desorption isotherms (BET), scanning electron microscopy (SEM), and UV-Visible absorption spectra. Hydrogen production tests were performed in aqueous methanol solutions under simulated sunlight. The results demonstrated that 130-times greater increase in hydrogen production rate was observed by the addition of BCL than individual TiO2. This better hydrogen production rate can be attributed to the increase in the amount of reduction equivalent of the system due to the oxidation of protein peptides caused by TiO2. In conclusion, the results indicate that hydrogen production efficiency can be significantly improved when integrating TiO2/MgCl2 with BCL. (C) 2022 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: hydrogen production; Lipase; Nano-conjugated enzymes; Photocatalyst; Solar radiation; Titanium dioxide

Facile fabrication of nano silver phosphate on B-doped g-C3N4: an excellent p-n heterojunction photocatalyst towards water oxidation and Cr (VI) reduction - Sahoo, Mitarani; Babu, Pradeepta; Singh, Chandrodai Pratap; Krishnamurty, Sailaja; Parida, Kulamani (Journal of Alloys and Compounds, 2022)
A photostable Ag3PO4/BCN type-II p-n heterojunction has been demonstrated by loading nano Ag3PO4 on B-doped g-C3N4 nanosheet (BCN). The photocatalysts were successfully characterized by various physicochemical techniques and their photocatalytic activities were tested towards the water oxidation reaction to produce oxygen and Cr (VI) reduction under visible light. The HRTEM confirms Ag3PO4 with a particle size of 15 nm has been deposited on BCN to construct a p-n heterojunction. The BCNS-50 absorbs more visible light in the solar spectrum as compared to other catalyst, demonstrating the ability to generate 587 mu mol h(-1)g(-1) O-2 and reduces 98% of 20 ppm Cr (VI) solution in 1 h. The lower PL intensity as well as lower arc value in case of BCNS-50 suggests the maximum e-h separation and lower charge transfer resistance across the semiconductor/electrolyte interface. The BCN sheet provides a compact heterojunction where the oxidation peak of Ag3PO4 decreases gradually and disappear in case of BCNS-50 suggesting the enhance stability of Ag3PO4 in the heterojunction. BCNS-50 could able to produce -139 and 3087.5 mu A photocurrent both in cathodic and anodic direction which is approximately 7 and 2.4 folds higher as compared to nano Ag3PO4. The generation of photocurrent in both cathodic and anodic direction confirms the formation of p-n heterojunction which further supported by Mott-Schottky analysis. Furthermore the construction of the p-n heterojunction is verified via Mott-Schottky study. DFT calculation explains the contribution of various atomic orbital of Ag3PO4 and BCN towards the formation of hybrid orbital in the heterojunction and the path for charge delocalization between them. This work may provide a limelight and alternative pathway for enhanced photocatalytic performance on construction of the p-n heterojunction in a simple way. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: Cr (VI) reduction; Density functional theory; Interfacial zone; p-n heterojunction; Photocatalyst; Water oxidation